Pengaruh Insentif Finansial, Insentif Non Finansial dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan pada PT. Tiara Cipta Nirwana - Lantara, I Made Rai Buda; Utama, I Wayan Mudiartha (E-Jurnal Manajemen; Vol 3 No 4 (2014), 2014)
Job satisfaction is an emotional state that is considered pleasant or unpleasant for employees in carrying out their work. An organization must consider the factors that may affect job satisfaction which are financial incentive s , non- financial incentives, an d environmental working situation . The purpose of this research is determin ing the effect of financial incentives, non- financial incentives, and environment al working situation on employee job satisfaction. The research is conducted in PT. Tiara Cipta Nirwana which is a private electrical contractor company in Bal i , with a total population sample of 101 respondents. The data analysis technique is multiple linear regression. financial incentives, non- financial incentives, and environment al working situation simultaneously have significant effect on employee job satisfaction. Partially non-financial incentives is the only variable that has no effect on job satisfaction and environmental working situation is the most dominant influence on job satisfaction of employees at PT. Tiara Cipta Nirwan a. Keywords: incentives, environment al working , job satisfaction
Keywords: incentives, environmental working, job satisfaction